Proyecto para la creación de un Instituto Tecnológico Superior en la ciudad de Quito bajo las buenas prácticas del PMI en el período del 2018 al 2019 - Medina García, Karina Alexandra (2019)
Higher education in Ecuador is one of the regular education instances of the education system. The State is in charge structuring, operating and accrediting Higher Education Institutions. Currently, the Higher Education Organic Law (LOES) acknowledged degrees awarded by Technical and Technological Institutes as third level, therefore, gives greater possibility to create or strengthen new Institutions to have a better academic offer and provide the opportunity for many young people to access higher education so their profiles are more competitive at the workplace. This document presents the beginning and planning process for the Creation of a Higher Technological Institute project, based on the good practices of the Project Management Institute PMI. On the other hand, a market research is presented by analyzing the strategic places of the zone and the different environments that influence the project. Finally, in order to support the viability of the project execution, there is a financial study with its different indicators.